Strategizing for the Future: A Mixed Method Approach to Department of Education Employees Retirement Readiness and Lifestyle Planning (International Journal of Scientific Research and Management (IJSRM), 2024)
This study determines the relationship between the level of retirement readiness and the extent of the lifestyle of DepEd employees to come up with a retirement readiness program. This is an explanatory sequential mixed-method study, comprising a cross-sectional survey and interviews was undertaken. Retirement Readiness in terms of health, financial, and contingency planning was examined and the extent of the lifestyle of DepEd retired employees in terms of health, spending habits, and recreational activities were also explored. Survey data were analyzed using Microsoft Excel and SPSS using non-parametric statistics and qualitative data were analyzed using thematic analysis. Statistical results show that indicators in retirement readiness have a moderate level in terms of obtaining emergency funds and a moderate extent of lifestyle in terms of spending for their needs. This indicates that retirees need to strengthen their ability to establish savings for emergencies and prioritize their personal needs. Qualitative data shows that in the event of an emergency, essential resources to rely on include dependable communication channels, emergency substances, and the right of entry to emergency services some of these are having financial support from children and finding ways and means to generate funds. The results indicate the need for a retirement readiness program that moves beyond merely raising awareness and provides information on a positive health approach, good financial management, and improving socialization skills to provide a holistic approach to the retirement readiness of DepEd Employees.